DESIGN: AS A PLATFORM MARKETING OF SMALL AND MEDIUM MICRO ENTERPRISES (STUDY: PAGELARAN DISTRICT) - Renaldo, Riki; Fauzi, Fauzi (Institut Bakti Nusantara, 2023)
Every person who has completed education would want to find and get decent jobs and in accordance with their abilities. But over time the current job field is increasingly difficult to get because the competition for jobs is getting tougher. The system used by the Pagelaran subdistrict is still using the traditional system. While today the times are increasingly sophisticated along with the existence of modern technology. At the system development stage using the prototype method starting from designing the needs analysis, then designing the requirements for the application design program for small and medium sized businesses in the Android-based performance district such as designing program, system requirements and system discussions. With UML (Unified Modeling Language) in the form of use case diagrams, activity diagrams and class diagrams.